2010
DOI: 10.1113/expphysiol.2009.050369
|View full text |Cite
|
Sign up to set email alerts
|

Detraining losses of skeletal muscle capillarization are associated with vascular endothelial growth factor protein expression in rats

Abstract: The purposes of this study were as follows: (1) to examine basal vascular endothelial growth factor (VEGF) protein concentrations following 10 weeks of endurance training and after 7 days of detraining; and (2) to examine the acute VEGF protein response to a single 1 h exercise work bout in trained and detrained animals in relationship to changes in capillary indices following training and detraining. Thirty-three Sprague-Dawley rats were randomized into the following six groups: (1) control-basal; (2) control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
47
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 48 publications
17
47
1
1
Order By: Relevance
“…This was a robust response seen in several muscles of the distal hindlimb (i.e., soleus, gastrocnemius, plantaris) (Table ), each representing varying degrees of oxidative and glycolytic potential . Consistent with this observation, two prior studies involving exercise training in rats, have also found detraining‐induced capillary regression whilst basal muscle VEGF expression is elevated (Table ). These studies provide the seemingly provocative observation that physiologically mediated capillary regression is not dependent on the withdrawal of VEGF.…”
Section: Introductionsupporting
confidence: 63%
“…This was a robust response seen in several muscles of the distal hindlimb (i.e., soleus, gastrocnemius, plantaris) (Table ), each representing varying degrees of oxidative and glycolytic potential . Consistent with this observation, two prior studies involving exercise training in rats, have also found detraining‐induced capillary regression whilst basal muscle VEGF expression is elevated (Table ). These studies provide the seemingly provocative observation that physiologically mediated capillary regression is not dependent on the withdrawal of VEGF.…”
Section: Introductionsupporting
confidence: 63%
“…We were unsuccessful despite numerous attempts to get the LCR rats to run on the treadmill prior to the start of our intervention period at the Wayne State University laboratory. Based on our experience with exercise studies using rodent models [4, 5, 10, 22], the LCR rats became excessively stressed when placed on the treadmill and would not move off of the shock grid despite being shocked intermittently or when the shock grid was turned off. Similarly, when the rats were placed on the treadmill belt and then the treadmill turned on the rats would `ride' the belt and then stand on the shock grid.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with standard procedures in our laboratory [4, 5, 10, 22, 23], animals were anesthetized with sodium pentobarbital (60 mg×kg −1 i.p .) and the left plantaris muscle was removed.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies reported that a short period of detraining does not seem to significantly decrease capillary density of the previously trained muscle, possibly due to the concomitant decrease in muscle fiber area (Klausen et al, 1981; Coyle et al, 1984). However, more recent data suggest that only a short period of detraining is adequate to reverse training-induced angiogenic remodeling, as seen by the regression of capillary contacts and individual capillary-to-fiber ratio in the plantaris and soleus muscles of rats (Malek et al, 2010). These authors suggested that this was modulated by vascular endothelial growth factor (VEGF).…”
Section: Effects Of Physical Inactivity On Muscle Fatiguementioning
confidence: 99%